2010
DOI: 10.1021/la102649x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Trimethylaluminum Diffusion in Three-Step ABC Molecular Layer Deposition Using Trimethylaluminum, Ethanolamine, and Maleic Anhydride

Abstract: Hybrid organic-inorganic films were grown by molecular layer deposition (MLD) with a three-step ABC reaction sequence using (A) trimethylaluminum (TMA), (B) ethanolamine (EA), and (C) maleic anhydride (MA) at 90 °C. Very large steady state mass gains of 1854-4220 ng/(cm(2) cycle) were measured depending on reaction conditions. These mass gains are much larger than typical mass gains for surface reactions. The quartz crystal microbalance (QCM) mass profiles during the TMA reaction were consistent with TMA diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 31 publications
(59 reference statements)
4
60
0
Order By: Relevance
“…In later studies it was deduced that the growth process of the films is governed by the TMA diffusion into and out of the forming film, making the growth process strongly dependent on the TMA dose and purge times used. Also experiments carried out at 130 °C showed that the self-limiting growth could be only observed when the films remained thin [108]. According to nanointendation measurements conducted for the TMA+2-aminoethanol+furan-2,5-dione films deposited at 90 °C, the elastic modulus and Berkovich hardness were about 13 GPa and about 0.27 GPa, respectively [84].…”
Section: Reviewmentioning
confidence: 99%
“…In later studies it was deduced that the growth process of the films is governed by the TMA diffusion into and out of the forming film, making the growth process strongly dependent on the TMA dose and purge times used. Also experiments carried out at 130 °C showed that the self-limiting growth could be only observed when the films remained thin [108]. According to nanointendation measurements conducted for the TMA+2-aminoethanol+furan-2,5-dione films deposited at 90 °C, the elastic modulus and Berkovich hardness were about 13 GPa and about 0.27 GPa, respectively [84].…”
Section: Reviewmentioning
confidence: 99%
“…Atomic layer deposition (ALD) is an advanced thin-film-deposition technique based on sequential surface-saturated deposition cycles, where each gaseous precursor pulse is separated by a purging pulse of inert gas. So far, hybrid thin films based on various metal alkoxides, [22][23][24][25][26][27][28][29][30][31][32] carboxylic acids, [33][34][35][36] and amines [33,[37][38][39] have been produced. We attribute the steady growth of the Ti-AP hybrid to the following facts: (1) the AP molecule is heterobifunctional and consists of a stiff aromatic backbone; moreover, (2) the -Cl ligands in TiCl 4 are small enough not to cause steric hindrance.…”
Section: Introductionmentioning
confidence: 99%
“…A three-step alucone process (ABC) was developed using TMA, ethanolamine (EA), and maleic anhydride (MA) further expanding the possibilities of available organic reactants 50,70 . The GPC was much higher than the two-step process but also highly dependent on the process temperature varying from 24 Å/cycle at 90°C down to 4 Å/cycle at 170°C.…”
Section: Alucone and Zinconementioning
confidence: 99%
“…For films grown at 130°C only a ~5% decrease in thickness after the first few days of growth was observed, a significant improvement over the two step process. 70 Carboxylic acids, such as benzoic, fumaric, and maleic acid, were also used as the organic component in the alucone process 71,72 . The GPC was dependent on the chosen carboxylic acid precursor as well as the temperature of the reaction varying from as high as 11.9 Å/cycle to 2.4 Å/cycle.…”
Section: Alucone and Zinconementioning
confidence: 99%